Wattles in goats are associated with the FMN1/GREM1 region on chromosome 10. (3rd March 2015) - Reber, I.; Keller, I.; Becker, D.; Flury, C.; Welle, M.; Drögemüller, C.
Summary The presence of congenital appendages (wattles) on the throat of goats is supposed to be under genetic control with a dominant mode of inheritance. Wattles contain a cartilaginous core covered with normal skin resembling early stages of extremities. To map the dominant caprine wattles (W) locus, we collected samples of 174 goats with wattles and 167 goats without wattles from nine different Swiss goat breeds. The samples were genotyped with the 53k goat SNP chip for a subsequent genome‐wide association study. We obtained a single strong association signal on chromosome 10 in a region containing functional candidate genes for limb development and outgrowth. We sequenced the whole genomes of an informative family trio containing an offspring without wattles and its heterozygous parents with wattles. In the associated goat chromosome 10 region, a total of 1055 SNPs and short indels perfectly co‐segregate with the W allele. None of the variants were perfectly associated with the phenotype after analyzing the genome sequences of eight additional goats. We speculate that the causative mutation is located in one of the numerous gaps in the current version of the goat reference sequence and/or represents a larger structural variant which influences the expression of the FMN1 and/or GREM1 genes. Also, we cannot rule out possible genetic or allelic heterogeneity. Our genetic findings support earlier assumptions that wattles are rudimentary developed extremities.